Anthocyanin-Sensitized TiO2 Nanoparticles for Phenazopyridine Photodegradation under Solar Simulated Light. (30th May 2018) - Zyoud, Ahed H.; Saleh, Fedaa; Helal, Muath H.; Shawahna, Ramzi; Hilal, Hikmat S.
Abstract : Pharmaceutical wastes are emerging as water contaminants. Like other organic contaminants, it is necessary to find safe and economic methods to remove them from the water. In this work, anthocyanin was used as a natural dye sensitizer for the wide band gap nanosize rutile TiO 2 . The TiO 2 /Anthocyanin particles were supported on activated carbon particle surfaces. The resulting composite, which was prepared and characterized by different methods, was then used as a catalyst in the photodegradation of phenazopyridine (a model pharmaceutical contaminant) under a solar simulated light. Depending on experimental conditions, up to 90% of the contaminant was mineralized leaving no new organic products in the reaction mixture. The results show the feasibility of using the activated carbon-supported TiO 2 /Anthocyanin photocatalyst for pharmaceutical contaminant removal in water. The natural dye anthocyanin readily sensitized the TiO2 to visible light. The unsupported TiO2, with its nanosize particles, was not easy to recover by simple separation methods, while the activated carbon-supported catalyst was easily isolated by decantation after reaction cessation. Moreover, the recovered AC/TiO2 catalyst could also be regenerated by adding fresh anthocyanin sensitizer after recovery for further reuse. Keeping the contaminant molecules closer to the catalytic sites by adsorption, the support also enhanced the efficiency of photocatalyst.